BRACHYURAN CRABS (DECAPODA, BRACHYURA) ASSOCIATED WITH THE GREEN SPONGE AMPHIMEDON VIRIDIS (DEMOSPONGIAE) FROM ITAGUA BEACH, SOUTH-EASTERN COAST of BRAZIL - Alves, Douglas F. R. [UNESP]; Carvalho, Marcelo C. R.; Barros-Alves, Samara de P. [UNESP]; Cobo, Valter J. [UNESP] (Brill Academic Publishers, 2012)
This study provides information on the community structure of brachyuran crabs associated with the green sponge, Amphimedon viridis Duchassaing & Michelotti, 1864, from a beach on the south-eastern coast of Brazil. Monthly collections from May 2002 through August 2003 were carried out on the rocky bottoms off Itagua Beach (23 degrees 27'07 '' S 45 degrees 02'49 '' W). Crabs on the green sponge banks were hand-caught during snorkelling sessions, and 638 crabs belonging to 31 species, 19 genera, and 10 families were obtained. Biological parameters, including sponge volume, number of individuals, density, richness, diversity, evenness, and dominance changed considerably over time. Species recruitment and foraging habit are some of the factors that drive the richness, dominance, and diversity patterns of this community. The green sponge banks are important sites for recruitment, refuge, and feeding of many species of brachyurans. Therefore, they are also important for the conservation of this group on the south-eastern coast of Brazil.